ANALYSIS OF INSTITUTIONAL DEVELOPMENT OF VILLAGE-OWNED ENTERPRISES IN WATER RESOURCES MANAGEMENT - Amirul Mustofa; Litafira Syahadiyanti; Eny Haryati; Damajanti Sri Lestari (Halu Oleo University, 2024)
Sumber Maron Tourism Village Management is an innovative program implemented by Village-Owned Enterprises (VOEs) in Karangsuko Village, Malang Regency. This research aims to analyze the institutional development of VOEs in managing water resources in the Sumber Maron Tourism Village, Malang Regency. The data collection techniques used in this research are interviews and documentation. Data analysis was carried out qualitatively by interpreting data from interviews and various documents obtained in the research. Next, compare the data that has been presented with the theory of institutional development. The research results show that developing VOEs institutions in managing water resources can produce tourist villages that benefit the community, village government, and VOEs managers. Second, it was found that managers needed to prepare access to information about websites and social media optimistically. The recommendation is that in developing the Sumber Maron tourist village, a website should be immediately prepared for information access so potential visitors can quickly get information.